No association between posture and musculoskeletal complaints in a professional bassist sample. (1st September 2015) - Woldendorp, K.H.; Boonstra, A.M.; Tijsma, A.; Arendzen, J.H.; Reneman, M.F.
Abstract: Background: Professional musicians receive little attention in pain medicine despite reports of high prevalence of musculoskeletal complaints. This study aims to investigate the association between work‐related postures and musculoskeletal complaints of professional bass players. Method: Participants were 141 professional and professional student double bassists and bass guitarists. Data about self‐reported functioning, general and mental health status, location and intensity of musculoskeletal complaints and psychosocial distress were collected online with self constructed and existing questionnaires. Logistic regression analyses were performed to analyse associations between work‐related postural stress (including type of instrument and accompanying specific exposures) and physical complains, adjusted for potential confounders. Results: Logistic regression analyses revealed no association between complaints and the playing position of the left shoulder area in double bassists ( p  = 0.30), the right wrist area in the bass guitarists ( p  = 0.70), the right wrist area for the German versus French bowing style ( p  = 0.59). Conclusion: All three hypotheses were rejected. This study shows that in this sample of professional bass players' long‐lasting exposures to postural stress were not associated with musculoskeletal complaints. This challenges a dominant model in pain medicine to focus on ergonomic postures.